PROCESS - ORIENTED ARCHITECTURE: EFFECT OF A DESIGN METHODOLOGY ON OUTCOMES OF ARCHITECTURE STUDENTS - MOHAMMED, NAJEH MOHAMMED (Journal of Duhok University, 2017)
The research presents a comparative investigation of two teaching approaches for architectural design studio: process oriented verse product driven. The processes oriented approach can be defined as a series of actions or steps that are directed toward a specific aim, while product driven is an approach that sets the form of end product as the main guidance for design processes. The research aims at answering the key question of whether the process oriented approach leads to better learning outcomes for architecture students than the product driven one. The study will investigate outputs of design exercises from several architectural design studios at the department of architecture, which are applying either of the two approaches independently. The attempt is to examine the research hypothesis that the process oriented design can be a successful teaching methodology in any architectural department regardless the academic context of the department.